(untitled) - Barry, Max (New York, 2007)
Stephen Jones is a shiny new hire at Zephyr Holdings. From the outside, Zephyr is just another bland corporate monolith, but behind its glass doors business is far from usual: the beautiful receptionist is paid twice as much as anybody else to do nothing, the sales reps use self help books as manuals, no one has seen the CEO, no one knows exactly what they are selling, and missing donuts are the cause of office intrigue. While Jones originally wanted to climb the corporate ladder, he now finds himself descending deeper into the irrational rationality of company policy. What he finds is hilarious, shocking, and utterly telling.
Keywords: Young men,Corporations,Bussiness ethics,Corporate culture,Thiếu niên,Công ty,Đạo đức kinh doanh,Văn hóa doanh nghiệp; Fiction,Fiction,Fiction,Fiction,Tiểu thuyết,Tiểu thuyết,Tiểu thuyết,Tiểu thuyết